DIAGNÓSTICO PRELIMINAR DA POPULAÇÃO DE HIPERTENSOS E DIABÉTICOS DO BAIRRO GLÓRIA, IJUÍ-RS - FRASSON, ANA P. Z.; WINKELMANN, ELIANE R.; KOPF, ELOIZA C.; PETTENON, MARINEZ K.; BOTTARO, LVANIA M. (Salão do Conhecimento, 2013)
Resumo